2020
DOI: 10.1146/annurev-publhealth-040119-094119
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Health Equity in Public Health Practice: Frameworks, Promising Strategies, and Measurement Considerations

Abstract: This review describes the context of health equity and options for integrating equity into public health practice. We first discuss how the conceptualization of health equity and how equity considerations in US public health practice have been shaped by multidisciplinary engagements. We then discuss specific ways to address equity in core public health functions, provide examples of relevant frameworks and promising strategies, and discuss conceptual and measurement issues relevant to assessing progress in mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 60 publications
0
81
0
Order By: Relevance
“…The present study’s results should be interpreted in light of these generalizability restrictions. There is a plethora of evidence showing how the current medical systems in place disproportionately negatively affect certain marginalized populations ( Liburd et al, 2020 ). The present work generally fails to include these populations, and more research is indicated to better understand the impact of the pandemic within these populations.…”
Section: Discussionmentioning
confidence: 99%
“…The present study’s results should be interpreted in light of these generalizability restrictions. There is a plethora of evidence showing how the current medical systems in place disproportionately negatively affect certain marginalized populations ( Liburd et al, 2020 ). The present work generally fails to include these populations, and more research is indicated to better understand the impact of the pandemic within these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this highlights the need for formal adoption of a health equity lens at the systems level to anchor all aspects of the health equity agenda, including the critical aspect of prioritization. This must be a comprehensive lens that operates through recognition of and attention to the multiple intersecting sources of oppression and enactment of these within institutional structures that create inequities, as well as recognition of how power and privilege operate within health systems prioritization [24,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Careful consideration of how economic arguments, including costs effectiveness analyses, might be structured to explicitly weigh health equity is a potential strategy for attempting to counter this [ 58 60 ]. Development of health equity indicators and surveillance measures, including those related to structural determinants, are needed to demonstrate burden and gradients in health outcomes [ 61 , 62 ]. Moreover, this highlights the need for formal adoption of a health equity lens at the systems level to anchor all aspects of the health equity agenda, including the critical aspect of prioritization.…”
Section: Discussionmentioning
confidence: 99%
“…Liburd Leandris C (2020) et al supposed that government public health plays a core role in promoting the realization of the highest level of health for all people, including seeking fair access to high-quality health facilities, drugs, commodities and services. All functional departments of the public health system can strengthen cooperation to increase the opportunity for citizens to obtain the best health [17]. Xueshan Sun (2018) et al measured health equity from the perspective of health demand and medical seeking behavior [18].…”
Section: Introductionmentioning
confidence: 99%